Impact of natural neuromedin‐B receptor variants on iron metabolism. Issue 2 (16th December 2019) - Rametta, Raffaela; Dongiovanni, Paola; Baselli, Guido A.; Pelusi, Serena; Meroni, Marica; Fracanzani, Anna L.; Busti, Fabiana; Castagna, Annalisa; Scarlini, Stefania; Corradini, Elena; Pietrangelo, Antonello; Girelli, Domenico; et al.
Abstract: Iron overload heritability remains partly unexplained. By performing whole exome sequencing in three patients with a clinical phenotype of hemochromatosis not accounted by known genetic risk factors, we identified in all patients rare variants predicted to alter activity of Neuromedin‐B receptor (NMBR). Coding NMBR mutations were enriched in 129 patients with hereditary hemochromatosis or iron overload phenotype, as compared to ethnically matched controls, including 100 local healthy blood donors and 1000Genomes project participants (15.5% vs 5%, P = .0038 at burden test), and were associated with higher transferrin saturation in regular blood donors ( P = .04). Consistently, in 191 patients with nonalcoholic fatty liver, the most common low‐frequency p.L390 M variant was independently associated with higher ferritin ( P = .03). In 58 individuals, who underwent oral iron challenge, carriage of the p.L390 M variant was associated with higher transferrin saturation and lower hepcidin release. Furthermore, the circulating concentration of the natural NMBR ligand, Neuromedin‐B, was reduced in response to iron challenge. It was also decreased in individuals carrying the p.L390 M variant and with hemochromatosis in parallel with increased transferrin saturation. In mice, Nmbr was induced by chronic dietary iron overload in the liver, gut, pancreas, spleen, and skeletal muscle, while Nmb was downregulated in gut, pancreas and spleen. Finally, Nmb amplified holo‐transferrin dependent induction of hepcidin in primary mouse hepatocytes, which was associated with Jak2 induction and abolished by the NMBR antagonist PD168368. In conclusion, NMBR natural variants were enriched in patients with iron overload, and associated with facilitated iron absorption, possibly related to a defect of iron‐induced hepcidin release.